2012
DOI: 10.1007/s13402-012-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of LOXs and COX-2 on FAK activation and cell migration induced by linoleic acid in MDA-MB-231 breast cancer cells

Abstract: In summary, our findings show that LA induces FAK activation and cell migration in MDA-MB-231 breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 66 publications
3
37
0
Order By: Relevance
“…Specifically, treatment of MDA-MB-231 cells with 90 μM LA induces FAK activation and migration through a SRC, Gi/Go, COX-2, and LOXs-activity dependent pathway, whereas treatment of nonmalignant mammary epithelial cell line MCF10A with 60 μM LA mediates an EMT-like process. 5,11 In the present study, we demonstrate that treatment with LA increases IR and/or IGF1R expression in the breast cancer cell lines MDA-MB-231 and MCF-7. In contrast, LA does not regulate IR and IGF1R expression in non-tumorigenic MCF12A mammary epithelial cells and it is feasible that LA is only able to induce IR and IGF1R expression in breast cancer cells.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Specifically, treatment of MDA-MB-231 cells with 90 μM LA induces FAK activation and migration through a SRC, Gi/Go, COX-2, and LOXs-activity dependent pathway, whereas treatment of nonmalignant mammary epithelial cell line MCF10A with 60 μM LA mediates an EMT-like process. 5,11 In the present study, we demonstrate that treatment with LA increases IR and/or IGF1R expression in the breast cancer cell lines MDA-MB-231 and MCF-7. In contrast, LA does not regulate IR and IGF1R expression in non-tumorigenic MCF12A mammary epithelial cells and it is feasible that LA is only able to induce IR and IGF1R expression in breast cancer cells.…”
Section: Discussionsupporting
confidence: 58%
“…Supporting our proposal, LA induces migration through a LOXs-dependent pathway in MDA-MB-231 cells. 5 It remains to be investigated the specific members of LOXs and the eicosanoids that mediate the increase of IR and IGF1R expression. inhibitor AH7614 (A and B), the LOXs inhibitor NDGA or the SRC inhibitor PP2 (C and D) and stimulated with 90 μM LA.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that LA induces FAK activation and migration through a concentration-dependent manner in MDA-MB-231 cells, with a maximum of FAK activation and migration at 90 mM LA [20]. In addition, treatment of MCF10A cells with 60 mM LA induces an EMT-like process [11].…”
Section: Discussionmentioning
confidence: 94%
“…Particularly, LA is the major PUFA in the diet of adult population, and it has been estimated to be consumed at 15-20 g per day per person, with a plasma concentration of $275 mM [35][36][37]. In addition, LA induces FAK activation and cell migration in MDA-MB-231 cells, as well as an EMT-like process in MCF10A cells [11,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation